'Beltway Bandits' and 'Poverty Barons': For‐Profit International Development Contracting and the Military‐Development Assemblage. Issue 4 (21st May 2015) - Nagaraj, Vijay Kumar; Arsel, Murat
ABSTRACT This article examines the political economy of for‐profit international development contracting and its growing convergence with private military contracting. It attempts a genealogy of contemporary for‐profit development contracting, underlining how the ability of for‐profit development firms to leverage their simultaneous integration into the global corporate‐financial architecture and the global development regime has been central to their spectacular growth. The article maps specific modalities and opportunity structures — contracting vehicles and procurement practices; the politics of the market structure; the contract culture and vendorism; shared circuitries of knowledge and power — which are enabling for‐profit contractors to consolidate their influence over the international development regime. It also traces the blurring of boundaries between development and security and how this is shaped and used by development contractors and private military firms alike. The author highlights how a combination of corporate diversification and mergers and acquisitions has paved the way for a market‐led development‐security assemblage and the birth of the 'private military‐development corporation', which profits equally from war, peace, reconstruction and development. The study focuses largely on the USA and UK owing to the scale of their international development regimes and for‐profit development markets.